Potential utility of tree ring δ18O series for reconstructing precipitation records from the lower reaches of the Yangtze River, southeast China. Issue 8 (27th April 2016) - Xu, Chenxi; Ge, Junyi; Nakatsuka, Takeshi; Yi, Liang; Zheng, Huaizhou; Sano, Masaki
Abstract: In this study, we investigated the interannual and intraannual variabilities in the oxygen isotope composition (δ 18 O) preserved in the tree ring cellulose of Pinus taiwanensis in the lower reaches of the Yangtze River, southeast China, to explore its potential utility for precipitation reconstruction over the period of 1855–2013. Intraannual variations of tree ring cellulose δ 18 O show distinct annual cycles that are characterized by δ 18 O maxima in the early growth near the ring boundary and δ 18 O minima in the middle and late portions of the ring. Seasonal patterns of tree ring δ 18 O were influenced by August–October typhoons. The tree ring cellulose δ 18 O was measured in both young and old trees to test for the juvenile effect. The results revealed no significant differences in the mean values and long‐term trends in δ 18 O in the old and young trees. A response analysis indicated that tree ring δ 18 O correlated significantly with precipitation and relative humidity between May and October, and the δ 18 O chronology accounted for 37.4% of the actual variation in the May–October precipitation between 1951 and 2013. The extremely dry and wet years revealed by the tree ring δ 18 O‐based reconstructed precipitation also corresponded to actual local drought and flood events from the documentary records. Reconstructed precipitation showed significant relationship with central tropical Pacific sea surface temperature, which indicated that El Niño–Southern Oscillation (ENSO) exerted influences on May–October precipitation in the lower reaches of the Yangtze River. In addition, the relationship between ENSO and precipitation weakened between 1920 and 1940, and low variance of ENSO from 1920 to 1940 may result in the damped ENSO's influences on precipitation in southeast China. Key Points: The tree ring δ 18 O is a promising proxy to reconstruct precipitation No juvenile effect on tree ring δ 18 O is present for P. taiwanensis Most of extreme events that were identified by tree ring δ 18 O are recorded in the documentaries